Low prevalence of influenza A strains with resistance markers in Brazil during 2017–2019 seasons - Sousa, Thiago das Chagas; Martins, Jessica Santa Cruz Carvalho; Miranda, Milene Dias; Garcia, Cristiana Couto; Resende, Paola Cristina; Santos, Cliomar A.; Debur, Maria do Carmo; Rodrigues, Rodrigo Ribeiro; Cavalcanti, Andrea Cony; Gregianini, Tatiana Schäffer; Iani, Felipe Campos de Melo; Pereira, Felicidade Mota; et al. (Frontiers in Public Health, 2022)
The influenza A virus (IAV) is of major public health concern as it causes annual epidemics and has the potential to cause pandemics. Currently, the neuraminidase inhibitors (NAIs) are the most widely used anti-influenza drugs, but, more recently, the drug baloxavir marboxil (BXM), a polymerase inhibitor, has also been licensed in some countries. Mutations in the viral genes that encode the antiviral targets can lead to treatment resistance. Worldwide, a low prevalence of antiviral resistant strains has been reported. Despite that, this situation can change rapidly, and resistant strain surveillance is a priority. Thus, this study aimed to evaluate Brazilian IAVs antiviral resistance during 2017 to 2019 through the identification of viral mutations associated with reduced inhibition of the drugs, and by testing the susceptibility of IAV isolates to oseltamivir (OST), the most widely used NAI drug in the country. Initially, we analyzed 282 influenza A(H1N1)pdm09 and 455 A(H3N2) genetic sequences available on GISAID. The amino acid substitution (AAS) NA:S247N was detected in one A(H1N1)pdm09 strain. We also identified NA:I222V (n=6) and NA:N329K (n=1) in A(H3N2) strains. In addition, we performed a molecular screening for NA:H275Y in 437 A(H1N1)pdm09 samples, by pyrosequencing, which revealed a single virus harboring this mutation. Furthermore, determination of OST IC50 values for 222 A(H1N1)pdm09 and 83 A(H3N2) isolates revealed that all isolates presented a normal susceptibility profile to the drug. Interestingly, we detected one A(H3N2) virus presenting with PA:E119D AAS. Moreover, majority of the IAV sequences had the M2:S31N adamantanes resistant marker. In conclusion, we show a low prevalence of Brazilian IAV strains with NAI resistance markers, in accordance with what is reported worldwide, indicating that NAIs still remain as an option for the treatment of influenza infections in Brazil. However, surveillance of influenza resistance should be strengthened in the country for improving the representativeness of investigated viruses and the robustness of the analysis.